The Australian Twins Economic Preferences Survey - Nathan Kettlewell; Agnieszka Tymula (Institute of Labor Economics (IZA), 2021)
This paper describes the Australian Twins Economic Preferences Survey (ATEPS). The dataset comprises a wide variety of preference and behavioral measures (risk aversion, impatience, ambiguity aversion, trust, confidence) elicited using incentivised decision tasks. 1,120 Australian adult twins (560 pairs) completed the survey, making it one of the largest datasets containing incentivised preference measures of twins. As the survey was conducted during the COVID-19 pandemic, we also collected information on experiences related to the pandemic, along with a variety of questions on political attitudes and mental wellbeing. We hope that ATEPS can make a valuable contribution to social science and genetics research.
Keywords: D90; D91; I10; Y90; 330; economic preferences; twins; twin study